From Vision to Action: National Bleeding Disorders Foundation’s Roadmap for Achieving Health Equity, Diversity, and Inclusion - Keri L. Norris; Marissa Melton; Karina Lopez; Dawn Rotellini; Leonard A. Valentino (Health Equity)
Background: The National Bleeding Disorders Foundation (NBDF) consistently hears from lived experience experts about daily challenges preventing them from leading their best life and thriving physically, mentally, and emotionally. Dedicated to enabling people and families impacted by inheritable blood and bleeding disorders (BDs) to thrive, NBDF recognized that the impact of social determinants, disparities, and inequities of health must be addressed explicitly to achieve their mission. Methods: NBDF developed a health equity, diversity, and inclusion strategic direction for the coming decade in the context of collaboration with regional, national, and international partners. Drawing upon limited available data, extensive community consultation, and a thorough landscape scan, NBDF identified specific social determinants of health preventing health equity in the inheritable BDs community. Results: NBDF developed a model detailing the engaging, empowering, and elevating work individual, community, organizational, and institutional stakeholders must undertake to dismantle health equity barriers. Overarching priorities and strategies were established, providing leadership, and support was offered in the form of tools, resources, and expertise. Conclusion: Designed to be tailored to needs and capacities, this approach may be applied by other rare disorder communities to develop and operationalize their own health, equity, diversity, and inclusion strategic direction to advance social justice.